Sketsa Glocal Theology - Manase Gulo (Sekolah Tinggi Teologi Arastamar Bengkulu, 2020)
Local theology is a model of theology that existed in postmodernism that emphasized the theology of the local cultural context. It means emphasize the efforts to meet church traditions and Christian themes with the reality of the life of the people around them. Simple theology always understands local sources which consist of local rituals, everyday language, folk songs, proverbs and art buildings. By using these elements means a theologian theologically contextually. The theologian was present and lived with people and listened to their voices. In this case, the simple theology seeks to respect and use the wisdom that is in the local culture, so that local people can easily interpret that wisdom in the light of the Gospel. Therefore this article will contribute a thought on how to build a sketch of Glocal theology.